Achieving optimal cancer outcomes in East Africa through multidisciplinary partnership: a case study of the Kenyan National Retinoblastoma Strategy group. Issue 1 (December 2016) - Hill, Jessica; Kimani, Kahaki; White, Abby; Barasa, Faith; Livingstone, Morgan; Gallie, Brenda; Dimaras, Helen
Abstract Background Strategic, interdisciplinary partnerships are essential to addressing the complex drivers of health inequities that result in survival disparities worldwide. Take for example the aggressive early childhood eye cancer retinoblastoma, where survival reaches 97 % in resource-rich countries, but is as low 30 % in some resource-limited nations, where 92 % of the burden lies. This suggests a need for a multifaceted approach to achieve a tangible and sustainable increase in survival. Methods We assembled the history the Kenyan National Retinoblastoma Strategy (KNRbS), using information documented in NGO reports, grant applications, news articles, meeting agendas and summaries. We evaluated the KNRbS using the principles found in the guide for transboundary research partnerships developed by the Swiss Commission for Research Partnerships with Developing Countries. Results A nationally co-ordinated approach drawing input and expertise from multiple disciplines and sectors presented opportunities to optimise cure of children with retinoblastoma. Annual meetings were key to achieving the over 40 major outputs of the group's efforts, related to Awareness, Medical Care, Family Support and Resource Mobilization. Three features were found to be critical to the KNRbS success: multidisciplinarity, consistency and flexibility. Conclusion The KNRbS has achieved a number of key outputs with limited financial investment. As a partnership, the KNRbS meets most of the criteria identified for success. Challenges remain in securing the long-term sustainability of its achievements. Elements of the Kenyan National Retinoblastoma Strategy may be useful to other developing countries struggling with limited survival of retinoblastoma and other cancers or rare diseases.